Attitude to family values - Grigoryeva O. V., Zakharova D. I. (Interactive science, 2017)
family is a system of a person’s social functioning. The article consists of the survey that was conducted April, 7–11, 2017, among students from NEFU: “Attitudes of teenagers to family values”. The study involved 150 students from NEFU. The aim of the research is to determine the level of teenagers’ readiness for family life and the factors affecting the creation of a new family. This analysis showed that most students are not ready to marry and have a wrong idea of ​​creating a family.
Keywords: дети; Семья; молодежь; студенты; брак; Республика Саха (Якутия); students; family; children; teenagers; marriage; Republic of Sakha (Yakutia)